Role of ficus carica Leaves Extract in Treatment of Hypothyroidism (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study was conducted to demonstrate the role of  alcoholic extract from ficus carica leaves in the treatment  of  hypothyroidism disease which induced by carbimazole drug. Forty  male rats were divided into five  groups,  eight  for each . group I selected as negative control  and administered orally with normal saline alone, group II served as positive control and treated by carbimazole anti-thyroid  drug for six weeks ,  group  III  was treated by plant extract (500 mg /kg, bw) for six weeks, the  fourth group IV was treated by carbimazole drug (5 mg) for six week to induce hypothyroidism   and then  treated by plant extract (500 mg /kg , bw) , and the fifth V group was  treated by thyroxin drug (100 mg) for six week instead of plant extract.         The results showed  insignificant differences (P